2007
DOI: 10.1007/s10535-007-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stage as a possible factor affecting cytokinin content and cytokinin dehydrogenase activity in Pinus sylvestris

Abstract: In the present study cytokinin dehydrogenase (CKX) activity was for the first time found in a conifer species, Pinus sylvestris. The activities were correlated with the endogenous cytokinin contents. Several enzyme substrates and two different electron acceptors were used to search for the enzyme activity in the extract from seeds, seedlings and plantlets. The highest specific activity was found in one-year-old plantlets with isopentenyladenine as the substrate and 2,6-dichlorophenolindophenol as the electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In addition, we analysed the endogenous concentrations of different CK types and CK metabolites in an attempt to study if the exogenous CKs act per se or through the changes of endogenous ones. Moreover, we tried to relate the endogenous phytohormones content with the organogenic response observed in the buds as some authors have argued for the importance of different CK metabolites, auxin or ABA as markers of the physiological stage of an explant in angiosperms (Moncaleán et al ) and gymnosperms (Valdés et al ).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, we analysed the endogenous concentrations of different CK types and CK metabolites in an attempt to study if the exogenous CKs act per se or through the changes of endogenous ones. Moreover, we tried to relate the endogenous phytohormones content with the organogenic response observed in the buds as some authors have argued for the importance of different CK metabolites, auxin or ABA as markers of the physiological stage of an explant in angiosperms (Moncaleán et al ) and gymnosperms (Valdés et al ).…”
Section: Discussionmentioning
confidence: 88%
“…Since Z-type cytokinins are derived from iP-type compounds and not vice versa (Kakimoto 2003;Sakakibara 2006), the low ratio of Z-to iP-cytokinins indicates lower activity of cytokinin synthesis. It has been suggested that Z/iP is a useful index of ageing and vigour in radiata (Valdés and et al 2002; and Scots pine (Valdés et al 2007). In Douglas-fir, concentrations of Z-type cytokinins were relatively higher in female and vegetative buds, whereas iP-type cytokinins were higher in male buds (Morris et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the differential compartmentalization of cytokinins may play a role in long-distance signalling (Corbesier et al 2003;Hirose et al 2008). In conifers, attention has been paid to the ratio of Z-type to iP-type cytokinins, but this has been mainly in the context of tree ageing or vigour (Valdés et al 2002(Valdés et al , 2003(Valdés et al , 2007 and not in reproduction.…”
Section: Introductionmentioning
confidence: 99%